A Polymerization‐Cutting Strategy: Self‐Protection Synthesis of Thiol‐Based Nanoporous Adsorbents for Efficient Mercury Removal. Issue 54 (31st August 2018) - Xu, Yang; Wang, Tianqi; He, Zidong; Zhou, Minghong; Yu, Wei; Shi, Buyin; Huang, Kun
Abstract: Highly toxic heavy metal ions such as mercury ions (Hg 2+ ) are a great threat to human life and the environment. Developing new strategies and materials to remove the toxic heavy metal ions has attracted more and more attentions. Herein a facile self‐protection synthesis of thiol‐based nanoporous adsorbents for efficient mercury removal via a polymerization‐cutting strategy is reported. The direct free‐radical polymerization of divinyl disulfide derivative and subsequently cutting off the disulfide linkage, without post‐synthesis or modification, can give rise to an exceptionally high density of thiol chelating sites. Moreover, the resultant thiol‐based nanoporous adsorbents (NAs‐SH) exhibit a high saturation uptake capacity (1240 mg g −1 ) and reused ability for mercury removal from water solution. The proposed polymerization‐cutting strategy may provide an alternative and cost‐effective method for the design and synthesis of various efficient nanoporous adsorbents at large scale in the future. Abstract : A facial self‐protection synthesis of thiol‐based nanoporous adsorbents via a polymerization‐cutting strategy was reported for the first time. The resultant thiol‐based nanoporous adsorbents (NAs‐SH) showed a high saturation uptake capacity of 1240 mg g −1 for Hg 2+ in the water and can be recycled four times.